(untitled) (Journal of Rashid Latif Medical College, 2024)
Introduction: In the modern era of advancement and technology, use of smart phones and laptops is common. Literature suggests that these digital devices have many negative effects on the health of humans. One of the most common adverse effects associated with prolonged use of mobile and laptop is neck pain. Methods: A cross-sectional study was carried out at University of Lahore from July 2022 to December 2022. A total of 206 undergraduate physical therapy students having age 18 to 25 years participated in the study. For data collection, smart phone & laptop usage and neck pain questionnaire was used. For data analysis, SPSS version 20 was used. Results: The mean age of the subjects was 21.15 ±1.89 years. The prevalence of neck pain was 82.5% (n=170). Neck pain was significantly associated (P-value< 0.05) with smart phone and laptop usage for greater than 4 hours. Surprisingly, neck pain was not associated (p valve>0.05) with different positions (standing/sitting/lying) in which students use smart phones for majority of the time, however, it had significant association (P-value< 0.05) with use of laptops in sitting position for majority of the time. Conclusion: The prevalence of neck pain is high in students who used smart phones and laptops for long hours Keywords: Back pain, Laptop, Neck pain, Phone, Students.